Insecticides resistance in the Culex quinquefasciatus populations from northern Thailand and possible resistance mechanisms - Jintana Yanola (2018)
© 2015 Elsevier B.V. The mosquito vector Culex quinquefasciatus is known to be resistant to insecticides worldwide, including Thailand. This study was the first investigation of the insecticide resistance mechanisms, involving metabolic detoxification and target site insensitivity in C. quinquefasciatus from Thailand. Adult females reared from field-caught larvae from six provinces of northern Thailand were determined for resistant status by exposing to 0.05% deltamethrin, 0.75% permethrin and 5% malathion papers using the standard WHO susceptibility test. The overall mortality rates were 45.8%, 11.4% and 80.2%, respectively. A fragment of voltage-gated sodium channel gene was amplified and sequenced to identify the knock down resistance (. kdr) mutation. The ace-1 gene mutation was determined by using PCR-RFLP. The L1014F kdr mutation was observed in all populations, but the homozygous mutant F/F1014 genotype was found only in two of the six provinces where the kdr mutation was significantly correlated with deltamethrin resistance. However, none of mosquitoes had the G119S mutation in the ace-1 gene. A laboratory deltamethrin resistant strain, Cq_CM_R, has been established showing a highly resistant level after selection for a few generations. The mutant F1014 allele frequency was significantly increased after one generation of selection. A synergist assay was performed to assess the metabolic detoxifying enzymes. Addition of bis(4-nitrophenyl)-phosphate (BNPP) and diethyl maleate (DEM), inhibitors of esterases and glutathione S-transferases (GST), respectively, into the larval bioassay of the Cq_CM strain with deltamethrin showed no significant reduction. By contrast, addition of piperonyl butoxide (PBO), an inhibitor of cytochrome P450 monooxygenases, showed a 9-fold reduction of resistance. Resistance to pyrethroids in C. quinquefasciatus is widely distributed in northern Thailand. This study reports for the first time for the detection of the L1014F kdr mutation in wild populations of C. quinquefasciatus in Thailand. At least two major mechanisms, kdr and cytochrome P450 monooxygenases, confer resistance to deltamethrin in Thai C. quinquefasciatus populations.